What motivates individuals with ADHD? A qualitative analysis from the adolescent's point of view. - Morsink, Sarah; Sonuga-Barke, Edmund; Mies, Gabry; Glorie, Nathalie; Lemiere, Jurgen; Oord, Saskia; Danckaerts, Marina (European Child & Adolescent Psychiatry, 2017)
Individuals with ADHD appear to respond differently to incentives than their peers. This could be due to a general altered sensitivity to reinforcers. However, apart from differences in the degree of motivation, individuals with ADHD might also be motivated by qualitatively different factors. This study aimed to harvest a range of motivational factors and identify ADHD-related qualitative differences in motivation, from the adolescent's point of view. Semi-structured interviews allowing participants to describe what motivates them in daily life were conducted with young adolescents (9-16 years) with and without ADHD. Thematic analysis was undertaken using NVivo software. Major themes relating to motivation were identified from the interview data. These were: (1) achieving a sense of togetherness; (2) feeling competent; (3) fulfilling a need for variation; (4) gaining pleasure from applying effort to achieve a goal; (5) valuing social reinforcement; (6) desiring to be absorbed/forget problems; (7) feeling free and independent, (8) attaining material reinforcement; and (9) an enjoyment of bodily stimulation. The theme structure was very similar for both groups. However, individuals with ADHD differed in some specifics: their focus on the passing of time, the absence of preference for predictable and familiar tasks, and their less elaborate description of the togetherness theme. A broad range of motivational themes was identified, stretching beyond the current focus of ADHD research and motivational theories. Similarities and differences in motivational values of individuals with and without ADHD should be taken into account in reward sensitivity research, and in psychological treatment.